2020
DOI: 10.1186/s12991-020-00301-7
|View full text |Cite
|
Sign up to set email alerts
|

The anxious aspects of insecure attachment styles are associated with depression either in pregnancy or in the postpartum period

Abstract: Background Perinatal depression (PND) is a major complication of pregnancy and many risk factors have been associated with its development both during pregnancy and postpartum. The transition to motherhood activates the attachment system. The aim of our study was to investigate the relationship between women’s attachment style (AS) and PND in pregnancy, and 1 month after childbirth, in a large cohort of women. We hypothesized that different patterns of AS were associated with either antenatal o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
3
12
1
Order By: Relevance
“…Consistent with our previous findings, stressful life events in the preceding 12 months were the strongest risk factor for perinatal depression [ 24 ]. Pregnancy itself is a stressful time with many potential changes and challenges.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous findings, stressful life events in the preceding 12 months were the strongest risk factor for perinatal depression [ 24 ]. Pregnancy itself is a stressful time with many potential changes and challenges.…”
Section: Discussionsupporting
confidence: 92%
“…An insecure attachment style is a stronger predictor of postpartum depression than prenatal depression and a history of mood disorder [ 22 ]. In a previous large study, we found that several subtypes of insecure attachment were associated with the onset of depression during pregnancy or after delivery [ 24 ]. The “need for approval” dimension, characterized by low self-confidence and excessive dependence on others, increases the risk of depression in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The Edinburgh Postnatal Depression Scale (EPDS) by Cox et al (17) is a validated tool for the clinical detection of PD and depressive symptoms during pregnancy (see description in the "Materials and methods" section). The insecure attachment is also considered to be a psychological factor associated with a higher risk of PD since it is related to internal working models based on a negative self-representation (18,19). Finally, the subjective vulnerability to develop PD is associated with dysfunctional coping strategies as well as protective factors for PD, which are related to personal psychological factors of resilience (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…The secure attachment style supports women’s interpersonal functioning, protects them from depression, and is associated with more effective emotional regulation strategies that improve the relationship with the child. Conversely, the insecure attachment style increased the risk of mood disorders, as bonding with the child can be perceived as a source of stress [ 43 ]. Furthermore, for the first time, we demonstrated that the relationship that the women in this study had with their parents in the first 15 years of their lives influenced their relationship with the newborn and breastfeeding.…”
Section: Discussionmentioning
confidence: 99%